The Influence of Parenting Patterns, Self-Perception, and Social Support on the Emotional Well-Being of Adolescents in Indonesia - Tamaulina Br Sembiring; Sitti Rabiah Yusuf; Eko Sudarmanto; Murthada Murthada (The Eastasouth Journal of Social Science and Humanities, 2023)
This study explores the complex connections between Indonesian adolescent emotional wellbeing, social support, self-perception, and parenting style. Using a mixed-approaches strategy, 350 adolescents between the ages of 13 and 18 were randomly selected and then subjected to both quantitative surveys and qualitative interviews. The quantitative results showed a strong correlation between more emotional well-being and authoritative parenting. Higher levels of self-perception—including self-efficacy and self-esteem—were associated with better emotional results. Robust family support was found to be a significant predictor of improved emotional well-being, and supportive peers and schools were also found to be beneficial. Depth was given by qualitative insights, which disentangled the complex experiences of parenting philosophies, self-perception, and social support. The amalgamation of both quantitative and qualitative findings provides a thorough comprehension of the elements influencing the psychological welfare of teenagers in Indonesia. There is discussion of the implications for interventions and policies aimed at promoting mental health in this population.